Kajian Etnobotani, Etnomedisin, dan Etnoekonomi Kencur (Kaempferia Galanga) pada Masyarakat Desa Klambu Kabupaten Grobogan - Muhammad Naufal Muzakki; Afida Rosyida; Intan Nur Fatikha; Adieba Warda Hayya (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Kencur (Kaempferia galanga L.) is one of the traditional medicinal plants that has long been used by the Indonesian people, including the community of Klambu Village, Klambu Subdistrict, Grobogan Regency. However, local knowledge regarding its use has not been widely documented scientifically. This study aims to examine the utilization of kencur by the local community from ethnobotanical, ethnomedicinal, and ethnoeconomic perspectives. The research method used is descriptive qualitative, with field surveys, direct observations, and structured interviews conducted with 35 respondents selected through snowball sampling techniques. The results show that the most commonly used parts of the kencur plant are the rhizome (fruit), leaves, and roots, which are used to treat ailments such as cough, colds, gastritis, and diarrhea, through various methods of preparation including chewing, drinking, applying topically, and cooking. In addition to its medicinal use, kencur also has economic value as it is sold in fresh form and as an ingredient in traditional herbal medicine (jamu). This knowledge is passed down through generations and is still preserved today. Therefore, kencur plays an important role in the lives of the Klambu Village community, both as a source of traditional medicine and as a local economic potential that should be preserved and developed. This research emphasizes the importance of preserving traditional knowledge based on medicinal plants and supports its development through systematic documentation, integration of pharmaceutical sciences, and local economic empowerment.